Contextualización reticular de la Responsabilidad Social Empresarial global y el desarrollo bioregional en Ciudad Juárez, Chihuahua-El Paso, Texas - María Luisa Picard-Ami Vogan; Tomás J. Cuevas Contreras (Nóesis)
The study proposes to approach the phenomenon by providing a networking context to Corporate Social Responsibility, the influences it receives from globalization, and the way it influences the bioregional borderland development of Ciudad Juarez and El Paso. The lens of social responsibility serves to examine a return to the private and social contextualization which occurs when an enterprise proactively uses its capacity to invest its resources on the benefit of society. In doing so, it contributes to creating an environment for investment and sustainable socioeconomic and sociopo litical growth by tapping into the support of different stakeholders and by capitalizing on transnational and personal and institutional networks. This study will use social network analysis to analyze the civic, corporate and governmental sectors in Ciudad Juarez, Chihuahua, and El Paso, Texas, and the proposed actions in the past decade to promote bioregional economic development.